The elderly-friendly housing neighbourhood preferred features by generations in Malaysia - Ismail, Hafiszah; Johaimi Ling, Nur Lesya Firsya; Abdul Wahab, Maszuwita; Mohd Fawzy, Faza Fayza; Mohamed Shaari, Shazwan; Anthony Jiram, Wilson Rangga (UiTM Press, 2025)
The continuous rise of the ageing population requires more attention to the refined concept of Elderly-Friendly (EF) Housing Neighbourhoods to meet the diverse needs of the elderly (seniors). The EF housing concept is an Age-Restricted Housing Concept with Assisted and Non-Assisted types. This study aims to outline the Elderly-Friendly Housing Neighbourhood Preferences Features of Malaysian Generations. The objectives of this study: (i) To define the generations; (ii) To identify the Elderly-Friendly Housing Neighbourhoods' Preference Features; and (iii) To determine the main preferred features of Elderly-Friendly Housing Neighbourhoods by Generations in Shah Alam, Selangor. The generations here refer to The Baby Boomers, Generation X (Gen-X), Generation Y (Gen-Y), and Generation Z (Gen-Z). The study adopted a mixed-methods approach. The five (5) main Elderly-Friendly Neighbourhood Preferences Features derived: (i) Services and Facilities, (ii) Physical Environment, (iii) Design, (iv) Location, and (v) Social. This study offers vital information to the housing providers, which will assist in providing better housing for the elderly (seniors).